1989
DOI: 10.1002/ajmg.1320340418
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of familial hypercholesterolemia in Johannesburg Jews

Abstract: The prevalence of heterozygous familial hypercholesterolemia was determined in a representative sample of 403 young Jewish men resident in Johannesburg, South Africa. Preliminary screening by measurement of serum total cholesterol demonstrated that 25 of them had levels greater than or equal to 7.5 mmol/l (290 mg/dl). On the basis of subsequent clinical, biochemical, and family studies, 6 men, or about 1 in 67 of the total sample, were considered to be heterozygotes. This very high prevalence, about 7 times gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 4 publications
0
31
0
3
Order By: Relevance
“…A frequency of FH ranging from 1/411 (0.24%) for North Karelians of Finland [24] to 1/67 (1.5%) for Ashkenazi Jew in South Africa [25]. The frequency of FH is 1/900 (0.11%) for Japanese in Asia [26].…”
Section: Discussionmentioning
confidence: 98%
“…A frequency of FH ranging from 1/411 (0.24%) for North Karelians of Finland [24] to 1/67 (1.5%) for Ashkenazi Jew in South Africa [25]. The frequency of FH is 1/900 (0.11%) for Japanese in Asia [26].…”
Section: Discussionmentioning
confidence: 98%
“…In ADH cohorts, mutation detection rates vary - as high as 90% in ethnically homogenous populations (4-8) and as low as 40% in our ongoing study of ADH in a multiethnic US cohort (9). For the 10-60% of ADH patients without detectable causal mutations (unexplained), a few differences have been reported when compared with FH patients: unexplained ADH patients have lower baseline LDL-C levels, higher high density lipoproteincholesterol (HDL-C) levels, and lower prevalence of tendon xanthomas (6,9-14).…”
Section: Introductionmentioning
confidence: 93%
“…A nationwide FH screening program among patients who were referred to the molecular diagnostic laboratory of the Academic Medical Center in the Netherlands reported that the frequency of HoFH was 1/300,000 based on a genetic test, and the calculated frequency of HeFH was 1/244 12) . Higher heterozygous frequencies ranging from 1/400 to 1/67 were also found in the Finns, French Canadians, Indians in South Africa, Christian Lebanese, and Afrikaners in South Africa, which may result from the founder effect [13][14][15][16][17][18][19] . Increasing efforts have been focused on early detection and earlier treatment of FH patients worldwide.…”
Section: Frequency Of Fh In Asian Populationsmentioning
confidence: 99%